Ruthenium Catalysts Supported on Hydrothermally Treated Carbon from Rice Husk: The Effect of Reduction Temperature on the Hydrogenation Reaction of Levulinic Acid to γ-Valerolactone - Rodriguez, Virginia Ines (2023)
Ru catalysts supported on activated carbon obtained by hydrothermal treatment of rice husk were evaluated in the hydrogenation reaction of levulinic acid to g-valerolactone. The hydrothermally treated carbon was characterized by nitrogen physisorption, elemental analysis, and thermogravimetric analysis, and the catalysts were characterized by FTIR spectroscopy, X-ray photoelectron spectroscopy, temperature-programmed reduction, and temperature-programmed desorption of pyridine (acidic properties). Prior to the reaction, the catalysts were reduced at different temperatures in the range of 100–350 C to evaluate the effect of the reduction temperature on the performance in the hydrogenation of levulinic acid. The reaction was carried out in a batch reactor at 70 C and 1.5 MPa. The results of conversion and selectivity to g-valerolactone showed that the catalyst with the best performance was the sample reduced at 200 C. After 2 h of reaction, a g-valerolactone yieldof 74% was achieved. This catalyst presented the lowest acidity value, and the ruthenium-containing phase consisted mainly of RuO2, with a small portion of Ru0. The solid catalyst can be recovered and successfully reused for three runs with the GVL yield at 56%.